2015
DOI: 10.1002/pros.23111
|View full text |Cite
|
Sign up to set email alerts
|

GSTP1 Loss results in accumulation of oxidative DNA base damage and promotes prostate cancer cell survival following exposure to protracted oxidative stress

Abstract: BACKGROUND Epigenetic silencing of glutathione S-transferase π (GSTP1) is a hallmark of transformation from normal prostatic epithelium to adenocarcinoma of the prostate. The functional significance of this loss is incompletely understood. The present study explores the effects of restored GSTP1 expression on glutathione levels, accumulation of oxidative DNA damage, and prostate cancer cell survival following oxidative stress induced by protracted, low dose rate ionizing radiation (LDR). METHODS GSTP1 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…8, 4446 Hence, DNA methyltransferases (DNMTs) and histone deacetylases (HDACs), which induce DNA methylation and histone acetylation modification and gene expression silencing are becoming new targets for prostate cancer prevention and therapy. 17, 4749 We previously reported that Nrf2 is epigenetically silenced by hypermethylation of the first five CpG islands during prostate cancer development in TRAMP mice and TRAMP-C1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8, 4446 Hence, DNA methyltransferases (DNMTs) and histone deacetylases (HDACs), which induce DNA methylation and histone acetylation modification and gene expression silencing are becoming new targets for prostate cancer prevention and therapy. 17, 4749 We previously reported that Nrf2 is epigenetically silenced by hypermethylation of the first five CpG islands during prostate cancer development in TRAMP mice and TRAMP-C1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological, experimental and clinical studies have suggested an association between oxidative stress and risk of PCa development and progression. 811 Excessive ROS induce DNA damage and mutation and cell and tissue damage, which could give rise to a variety of human pathogenesis, including cardiovascular, metabolic, inflammatory, and neurodegenerative diseases and cancer. 1214 …”
Section: Introductionmentioning
confidence: 99%
“…Presumably, the telomerase activity in the postulated epithelial progenitor cells and stem-like cells in BPH would not safeguard against genomic insults from ROS. However, glutathione S -transferase P (GST-P), which is expressed in normal prostate and BPH but not in HGPIN or prostate cancer 107,108 , does have activity against reactive oxidants and electrophiles that could damage DNA 109,110 . Perhaps, BPH is not susceptible to telomere shortening from hyper-proliferation and oxidative DNA damage because of the maintenance activity of telomerase in postulated epithelial progenitor cells and stem-like cells 57 and the detoxification activity of GST-P 50 , respectively.…”
Section: Telomeres and Genomic Alterationsmentioning
confidence: 99%
“…It has been shown that promoter hypermethylation is an epigenetic mechanism able to repress gene transcription by inhibiting the binding of transcription factors to their consensus sequences when methylated (Herman & Baylin, ). In the studies cited above, downregulation of GSTP1 gene expression was associated to an aberrant methylation in the promoter region (Chan et al., ; Li et al., ; Lin et al., ; Martignano et al., ; Mian et al., ; Shilpa et al., ; Zelic et al., ; Zhang et al., ). Moreover, promoter methylation of GSTP1 gene was detected in some body fluids of patients with prostate cancer and was proposed as a biomarker candidate for noninvasive detection of prostate cancer (Cairns et al., ; Goessl et al., ).…”
Section: Introductionmentioning
confidence: 99%